2021
DOI: 10.1038/s41598-021-95870-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antimicrobial susceptibility profiles of Nocardia species clinically isolated in Japan

Abstract: The aims of the present study were to profile the antimicrobial susceptibility patterns of a diverse range of Nocardia species isolated in Japan, and to determine the ability of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for species/complex identification. Identification of 153 clinical isolates was performed by full-length 16S rRNA gene sequencing as a reference method to evaluate the usefulness of MALDI-TOF MS identification. Antimicrobial susceptibility testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The rest of the sequences form clusters with different restriction patterns showing the discrepancy between strains of the same study species, thus conforming 6 more ribotypes. The results suggest the existence of subgroups within N. brasiliensis with more significant variability than previously reported 14 - 17 .…”
Section: Discussionsupporting
confidence: 42%
“…The rest of the sequences form clusters with different restriction patterns showing the discrepancy between strains of the same study species, thus conforming 6 more ribotypes. The results suggest the existence of subgroups within N. brasiliensis with more significant variability than previously reported 14 - 17 .…”
Section: Discussionsupporting
confidence: 42%
“…With the development of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS), the common clinical Nocardia species (e.g., N. cyriacigeorgica and N. farcinica ) can be identified rapidly. However, the available database of MALDI-TOF MS is limited for Nocardia strains leading to some uncommon isolates with no or false identification [ 10 , 11 ]. The 16S rRNA gene sequencing is generally considered as the primary means for accurate identification of the clinically encountered Nocardia isolates [ 12 ], but it cannot discriminate closely related species due to high conservation, unless it combines with a housekeeping gene, such as gyrB or rpoB [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, antimicrobial susceptibility varies widely between species based on CLSI M24-A 13 breakpoints. 4 Masahiro Toyokawa et al 14 showed that imipenem was 100% resistant to N. otitidiscaviarumand that linezolid had the highest sensitivity in in vitro susceptibility…”
Section: Discussionmentioning
confidence: 99%